USING DICTATION METHOD IN TEACHING ENGLISH LISTENING SKILL AT SEVENTH GRADE STUDENTS OF MTS 1 PAB HELVETIA - Aslamiah, Aslamiah (BRIGHT VISION Journal of Language and Education, 2023)
The  research  is  aimed  to   find out  the  following  question: Is the students’ listening skill taught by using Dictation Method better than without Dictation Method.   The sample of this     research   were   two classes, such as   30 students   at   VII C as experimental class and 30 students VII D as control class VII MTs PAB 1 Helvetia for the 2020/2021. The  finding  research  shows  that:  Dictation Method  prove  that  using it  can  make better  score  in  conducting  test, especially  in  listening skill. It looks from their   score. The analysis of the test used normality and homogeneity test, and analyzing the data used t-test formula. After  that,  the  writer  do; (1)   the  students listening skill   by   using   dictation method   got   the   meant   73,16   and standard deviation   is 12,55. (2)  the  students listening skill  without dictation method  got  the mean  65  and standard deviation is 12,86, The t-test results also show that t(observed) 2,45 is higher than t(table) at a significance level of 5% (0.05) with 58 degrees of freedom of 2.045. From the results of 2,45> 2.045 result in H0  (null hypothesis) rejected and Ha (alternative hypothesis) accepted. So that, the alternative hypothesis (Ha) proposed  is accepted  and  null  (Ho)  is  rejected.  So it can be conclude that   there  is  better  of using dictation method in listening skill.